Developing SIPCaR projects utilizing modern technologies: Its impact to students’ engagement, R&D skills, and learning outcomes - Acut, Dharel (LUMAT: International Journal on Math, Science and Technology Education, 2022)
Due to the onset of the COVID-19 pandemic, the education sector responded quickly to change the mode of delivering instructions to students in hybrid learning. Since in-school learning is no longer feasible, schools are devising teaching-learning pedagogies that are practical to achieving positive students' learning and quality instruction. This study aims to find out the impact of science investigatory projects, capstone projects, and robotics (SIPCaR) to students' engagement, and research and development (R&D) skills, and learning outcomes. Using purposive sampling and mixed-method research design, results revealed that students were very engaged, their R&D skills and learning outcomes proficiency are highly evident. Students were very cognitively engaged, behaviorally engaged, socially engaged, and moderately emotionally engaged, with means 4.27, 4.16, 4.41, and 3.44, respectively. Their R&D skills consist of analytical skills, information seeking skills, problem-solving skills, communication skills, and methodology skills are proficient with means 4.10, 4.06, 3.80, 4.30, and 3.78, sequentially. The findings of the study prove that, if appropriately implemented, SIPCaR projects open countless opportunities for students to achieve high-level learning outcomes, collaborate and innovate modern technologies that could potentially help emerging societal problems. Despite the challenges posed by the health crisis, STEM educators may formulate activities that result in students' holistic development in a remote classroom setting.